Gain and noise figure improvements in a shorter wavelength region of EDFA using a macrobending approach - Daud, S.A.; Emami, Siamak Dawazdah; Mohamed, K.S.; Yusoff, Norazriena M.; Aminudin, L.; Abdul-Rashid, Hairul Azhar; Harun, Sulaiman Wadi; Ahmad, Harith; Mokhtar, Mohd Ridzuan; Yusoff, Zulfadzli; Rahman, Faidz Abd (IOP Publishing, 2008)
Gain and noise figure improvements are demonstrated in a shorter wavelength region of a double-pass EDFA using a macrobending approach. The EDF is wound in a small radius to suppress the amplified spontaneous emission at the longer wavelength in order to achieve a high amplification in the shorter wavelength. Gain enhancements of about 12-14 dB are obtained with macrobending at the wavelength region between 1480 and 1530 nm. The macrobending also reduces the noise figure of the EDFA at wavelengths shorter than 1525 nm with a maximum improvement of 25 dB.